PERLINDUNGAN HUKUM TERHADAPKONSUMEN CAPIT COKELAT KEDALUWARSA DARI PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN: Consumer's Legal Protection Of The Expired Claw Chocolate From Legal Perspective Of Consumers Protections - Salsabila, Anzela; Anggraini, Anna Maria Tri (AMICUS CURIAE, 2024)
Online shopping has become very attractive in this day and age when it is easier for people to meet their needs and is considered easier from the standpoint of searching for goods, payment to delivery. Online sales can be made through TikTok Live and payments can be made through the online marketplace Shopee. This online shopping also has a weakness: in the transaction, the product that arrives may not match the product offered or even the product that arrives has expired. On this basis, questions arise about the liability of commercial actors in the sale of expired chocolate claws under the Consumer Protection Act and other relevant regulations as well as how customers can may pursue legal remedies against expired chocolate swipes under the Consumer Protection Act and other related regulations. This study uses a normative research method using primary data and secondary data, which are then analyzed using